Stimulation of Myocardial Na+-Independent Cl−-HCO3− Exchanger by Angiotensin II Is Mediated by Endogenous Endothelin - Camilión de Hurtado, María Cristina (2000)
Experiments were performed in isolated cat papillary muscles loaded with the pH-sensitive dye 2′,7′-bis(2-carboxyethyl)-5(6)-carboxyfluorescein in the esterified form to study the effect of endothelin-1 (ET-1) on the activity of the Na+-independent Cl−-HCO3− exchanger. Exposure to ET-1 (10 nmol/L) raised pHi by 0.13±0.03 U (P<0.05) in papillary muscles superfused with nominally HCO3−-free solution, whereas no significant change was detected under CO2/HCO3−-buffered medium. However, if ET-1 was applied to muscles pretreated with the anion exchanger inhibitor 4-acetamido-4′-isothiocyanato-stilbene-2,2′-disulfonic acid, pHi increased by 0.09±0.02 U (P<0.05) in the presence of CO2/HCO3− buffer. The rate of pHi recovery from trimethylamine hydrochloride–induced intracellular alkaline load was enhanced so that net HCO3 efflux increased about three times in the presence of ET-1 (2.74±0.25 versus 9.66±1.29 mmol · L−1 · min−1 at pHi 7.55, P<0.05). This effect was canceled by previous exposure to either 50 nmol/L PD 142,893 (nonselective endothelin receptor blocker) or 300 nmol/L BQ 123 (selective blocker of ETA receptors). BQ 123 also abolished angiotensin II–induced activation of the Na+ independent Cl−-HCO3− exchanger. These results show that ET-1 increases the activity of the Na+-independent Cl−-HCO3− exchanger in cardiac tissue through the ETA receptors. Furthermore, our data suggest that the previously described angiotensin II–induced stimulation of the anion exchanger activity is mediated by endogenous ET-1.